Tindak Ilokusi Deklaratif yang Diucapkan dalam Film “Cruella” - Pulungan, Febrina Sanjo; Ambalegin, Ambalegin (Universitas Putera Batam, 2022)
This research aimed at finding out the types of declarative illocutionary acts in the “Cruella” movie. The utterances of the characters were taken to be data of this research. It was analyzed by applying the types of declarative. The method of collecting the data was the observational method and non-participatory technique. In analyzing the data, the researchers used the pragmatic identity method and pragmatic competence- in equalizing. The results found out that there were 15 utterances of declarative acts uttered in “Cruella” movie. There were 15 declarative illocutionary acts uttered in the movie. The characters uttered declarative acts of a sentence, excommunicate, approve, and fire. There were some data in the movie, namely one data of sentence, four data of excommunicate, seven data of approve and three data of fire. It was found that the dominant type was the declarative act of approve. It became as dominant type because there were many utterances that needed to be approved by the speaker.